Estratégia de suprimento e governança no setor florestal: um estudo de caso múltiplo na indústria de base florestal do Rio Grande do Sul - Lisboa, Rodrigo da Silva (2009)
The present work had as central objective to research companies of forest base of Rio Grande do Sul to determine their mechanisms and strategies in the supply of raw material forest (MPF). Specifically, it analyzed the similarities and differences in the strategies and mechanisms for the supply of MPF that the companies use. This allowed the identification of the main governance structures as well as their main determinants. As a theoretical basis, the present work used the framework offered by New Institutional Economics (NEI), specifically the theories of the Economics of Transaction Costs (ECT), through its behavioral assumptions (limited rationality and opportunism) and the characteristics of transactions (asset specificity, frequency and uncertainty), and the Institutional Environment. This work is characterized as a multiple-case study, because it was used 5 companies as units of analysis. To obtain the data necessary for the execution of this study were held semi-structured interviews with companies, through key-informants nominated by them. It was concluded that the forest base companies use different strategies for their supply of MPF, since transactions carried through market until full production verticalized. It was noticed that the main determinant that takes the companies analyzed to integrate vertically through plantations themselves, partnerships and leasing of areas is the uncertainty in transactions for the supply of MPF. Other determinants that also mold the structures of the companies are: the formal and informal institutional environment, the increased demand for raw materials, the forest certification, the legitimacy before the society, among others.